Realisasi Desa Curug Menjadi Desa Wisata Di Kecamatan Gunung Sindur, Kabupaten Bogor - Kamaluddin Nashir, Asep; Kusumajanti, Kusumajanti; Widiastuti, Ni Putu Eka; Maryam, Siti; Ananda, Asri Dwi (Indonesian Journal of Society Engagement, 2024)
Curug Village, Gunung Sindur District, Bogor Regency has made efforts to become an edutainment tourism village. One year of mentoring by the UPNVJ PPDM Scheme PKM Team has made efforts to prepare Curug Village to become a tourism village by the Curug Village Government forming a Tourism Awareness Group, determining Kampung Sawah Pulo as a rice field tourism location. The residents' discussion in RT 03 RW 03, Curug Village has agreed to make their area a tourism location. Based on the results of the Social Economic Environmental Awareness study in realizing the Fish Edutourism Tourism Village in achieving economic independence, it is necessary to provide assistance to the Tourism Awareness Group so that this ideal can be realized. Support from the Village Government is the main requirement to make Curug Village a tourism village in addition to full support from all villagers. The Applied PKM / Community Partnership Team intends to assist in solving problems in realizing a tourism village in Curug Village from the fields of Group Communication, Finance, Diplomacy, Politics. The next goal is to realize community independence in Curug Village by taking on economic roles according to their abilities. In addition, this Applied PKM supports the achievement of the Sustainable Development Goals (SDGs) point eight, namely decent work and economic growth, especially in Curug Village. Optimization of the Tourism Awareness Group of the Sawah Pulo Village community in accordance with the urgency of the needs of the Curug Village community.